On Soft \(Ig^*\) Closed Sets in Soft Ideal Topological Spaces (Journal of Informatics and Mathematical Sciences, 2017)
In this paper we introduce and study the notions of soft \(Ig^{*}\) closed sets in soft ideal topological spaces and investigate some of their properties.
Keywords: Soft \(Ig\) closed sets; Soft \(Ig^{*}\) closed sets; \(sIg^{*}\) closure; \(sIg^{*}\) interior